2021
DOI: 10.1039/d1fo02288a
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet aggravates colitis, impairs intestinal barrier and alters gut microbiota and metabolism in DSS-induced mice

Abstract: A ketogenic diet was shown to aggravate DSS-induced colitis in mice by increasing intestinal and systemic inflammation, and disrupting the intestinal barrier, which results from modulated gut microbiota and metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 50 publications
3
33
1
Order By: Relevance
“…Additionally, the severity index of colitis measured by DAI scores was also decreased by ADMSCs transplantation (Figure 2C). Another typical morphological alteration in colitis mice is reductions in colon length (33). In this work, we found that the colon lengths of mice in the ADMSCs +DSS group were approximated to those in the control group, while mice in the DSS group exhibited significant reductions in colon length (Figure 2D).…”
Section: Admscs Transplantation Ameliorated Dss-induced Colitis and I...supporting
confidence: 54%
“…Additionally, the severity index of colitis measured by DAI scores was also decreased by ADMSCs transplantation (Figure 2C). Another typical morphological alteration in colitis mice is reductions in colon length (33). In this work, we found that the colon lengths of mice in the ADMSCs +DSS group were approximated to those in the control group, while mice in the DSS group exhibited significant reductions in colon length (Figure 2D).…”
Section: Admscs Transplantation Ameliorated Dss-induced Colitis and I...supporting
confidence: 54%
“…KD alters the gut microbiota in a manner different from a high-fat diet and elevates circulating ketone bodies, which inhibit the growth of Bifidobacterium and reduce the level of intestinal pro-inflammatory Th17 cells [ 179 ]. However, in another study, KD was found to aggravate DSS-induced colitis with increased pathogenic bacteria such as Proteobacteria , Enterobacteriaceae , Helicobacter and Escherichia–Shigella and decreased potentially beneficial Erysipelotrichaceae [ 180 ]. Moreover, the actual role of the KD on human beings with IBD remains unknown, and the health effects of long-term KD also require further studies.…”
Section: Dietary Strategies Alleviating Ibdmentioning
confidence: 99%
“…Researchers found that the KD significantly reduced inflammatory responses, protected intestinal barrier function, reduced innate lymphoid cell (ILC3) production, and reduced expression of related inflammatory cytokines as compared to LCD [ 66 ]. While the Kong et al study [ 66 ] suggested that a KD attenuated intestinal inflammation in a DSS murine colitis model, another study [ 67 ] showed the opposite findings. The Li et al study [ 67 ] aimed at exploring the effects of a ketogenic diet on IBD in mice and its potential mechanisms; mouse models were given a KD or a control diet (CD) for a month and IBD was induced by diluting drinking water with 2% DSS during the last week of the diet.…”
Section: Specific Dietary Interventionsmentioning
confidence: 99%